University Challenge: Critical Issues for Teaching and Learning, 1st edition - Harland, Tony (Routledge, 2020)
University Challenge: Critical Issues for Teaching and Learning offers a nuanced and critical reading of university teaching, particularly the pressures under which academics in neoliberal, mass higher education must operate.